Utilizing natural and engineered peroxiredoxins as intracellular peroxide reporters - Van Laer, Koen; Dick, Tobias P. (Molecules and cells, 2016)
Koen Van Laer, and Tobias P. Dick. Mol. Cells 2016;39:46-52. https://doi.org/10.14348/molcells.2016.2328
Gesehen am 04.06.2020